Flap Necrosis Associated With Furlow’s Palatoplasty - Percy Rossell‐Perry (My University, 2023)
BACKGROUND: Numerous authors have reported their outcomes after using Furlow's palatoplasty for cleft palate repair. However, little attention has been given to the operative complications associated with this technique. The present study was carried out to present cases and analyze the various factors influencing the development of this complication accompanying Furlow's palatoplasty. MATERIALS AND METHODS: This is a case report study of patients with cleft palate admitted to our center due to sequelae after primary cleft palate repair using Furlow palatoplasty between 2003 and 2021. Patient information was identified from the Smile Train cleft charity organization, parents' reports, and hospital records (intake forms and operating room registries). RESULTS: Five patients were identified as having secondary cleft palate with palatal flap necrosis and associated with Furlow palatoplasty during patient evaluation at our center between 2003 and 2021. The observed prevalence was 1.54%. CONCLUSIONS: Palatal flap necrosis is a rare but serious complication after primary Furlow's palatoplasty. The occurrence of this complication can be reduced by careful preoperative planning, and prevention is possible.
Keywords: Palatoplasty; Medicine; Complication; Dentistry; Surgery; Palatoplasty; Medicine; Complication; Dentistry; Surgery; Cleft Palate surgery; Cleft Palate surgery; Cleft Palate surgery; Cleft Palate surgery; Humans; Humans; Humans; Humans; Infant; Infant; Infant; Infant; Necrosis etiology; Necrosis etiology; Necrosis etiology; Necrosis etiology; Necrosis surgery; Necrosis surgery; Necrosis surgery; Necrosis surgery; Palate, Soft surgery; Palate, Soft surgery; Palate, Soft surgery; Palate, Soft surgery; Postoperative Complications surgery; Postoperative Complications surgery; Postoperative Complications surgery; Postoperative Complications surgery; Retrospective Studies; Retrospective Studies; Retrospective Studies; Retrospective Studies; Vascular Diseases; Vascular Diseases; Vascular Diseases; Vascular Diseases; Velopharyngeal Insufficiency surgery; Velopharyngeal Insufficiency surgery; Velopharyngeal Insufficiency surgery; Velopharyngeal Insufficiency surgery; Treatment Outcome; Treatment Outcome; Treatment Outcome; Treatment Outcome; Plastic Surgery Procedures adverse effects; Plastic Surgery Procedures adverse effects; Plastic Surgery Procedures adverse effects; Plastic Surgery Procedures adverse effects; Life Sciences Biochemistry, Genetics and Molecular Biology Genetics Cleft Lip and Palate Research; Health Sciences Medicine Surgery Reconstructive Surgery and Microvascular Techniques; Health Sciences Medicine Surgery Nasal Surgery and Airway Studies